Demystifying machine learning models for IOT attack detection with explainable AI - Muna, Rabeya Khatun; Maliha, Homaira Tasnim; Hasan, Mahedi (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.